English Learning Needs Analysis Of Accounting Department Students - Lantu, Ika Paramitha; Pampu, Fira Anwar S. (Sintuwu Maroso Journal of English Teaching, 2024)
The purpose of this research was to find out the English learning needs of students majoring in accounting at SMK Negeri 1 Ampana Kota, including target needs and learning needs. This research used a qualitative descriptive method, by distributing questionnaires to 32 students of class XI Accounting 1, interviewing the teacher and two students. This research uses the theory of Macalister and Nation, (2010). The findings from this research are, for the necessities of students is students need general English materials. For the lacks, students have difficulty finding friends who can be invited to communicate in English. Furthermore, for the wants of students is the student wants to master speaking skills in English. Then, supported by the teacher's role in fulfilling students’ learning needs is to search material from books and from internet for additional material if the books provided by the school are not completed. Furthermore, the student’s role in improving English skills, especially speaking skill is that students do not rely only on the material that has been given at school, but students can also study outside school hours by utilizing technology in the form of mobile phones or laptops, with learning concepts that are interest to each student